O fazer intelectual brasileiro (1930-1946): Rachel de Queiroz e o Congresso de 1946 - Alves, Plauto Daniel Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work aims to study two types of make up, or, if you prefer, the construction of the Brazilian intellectual, from an analysis of the self-conceptions of historical subjects that refers to hybridization - or the fusion of alien elements with other, internal reality of the actors - marked by expedients of persuasion (rhetorical) engendered by the agents to legitimize their own intellectual notions. In the first mode, we study the novels by Rachel de Queiroz and her trajectory, by aiming to show the universe of mediators and producers endowed with national visibility and proper literary rhetorical forms of the Romance of 1930s. Second, we focus on the literary experiences of a group of writers from Ceará little, the collective CLÃ, These scholars of bad luck made in 1946 a congress of writers whose main agenda is summarized in the problems of intellectual/province writer. Notion that showed the limitations that restricted their works and activities to the local dimension

Este trabalho enseja estudar duas modalidades do fazer-se, ou, caso se prefira, da formação do intelectual brasileiro, a partir de uma análise das autoconcepções dos sujeitos históricos que as aborda como uma hibridização - ou seja, a fusão de elementos alienígenas com outros, internos à realidade dos atores - marcada por expedientes de convencimento (retóricos) engendrados pelos agentes para legitimar as suas próprias noções de intelectual. Na primeira modalidade, a ser estudada a partir dos romances e da trajetória de Rachel de Queiroz, enseja-se acenar ao universo dos mediadores e produtores dotados de visibilidade nacional e às formas retóricas propriamente literárias do Romance de 30. Na segunda, se enfoca as vivências literárias de um grupo de escritores cearenses de pouco vulto nacional, o coletivo CLÃ. Estes letrados de pouca sorte realizaram no ano de 1946 um congresso de escritores cuja pauta principal se resume nos problemas do intelectual/escritor de província. Noção que ensejava aludir às limitações que restringiam suas obras e suas atividades à dimensão local
Keywords: Queiroz, Rachel de 1910-2003; História; Literatura brasileira; Direita e esquerda (Ciencia politica) - História; Intelectuais e politica; Brasil - História - Período colonial, 1500-1822